Transcriptome Profiling Based on Larvae at Different Time Points After Hatching Provides a Core Set of Gene Resource for Understanding the Metabolic Mechanisms of the Brood-Care Behavior in Octopus ocellatus - Bao, Xiaokai; Liu, Xiumei; Yu, Benshu; Li, Yan; Cui, Mingxian; Wang, Weijun; Feng, Yanwei; Xu, Xiaohui; Sun, Guohua; Li, Bin; Li, Zan; Yang, Jianmin (Frontiers in Physiology, 2022)
The metabolic processes of organisms are very complex. Each process is crucial, and affects the growth, development, and reproduction of organisms. Metabolism related mechanisms in Octopus ocellatus behaviors have not been widely studied. Brood-care is a common behavior in most organisms, which can improve the survival rate and constitution of larvae. O. ocellatus carried out this behavior, but it was rarely noticed by researchers before. In our study, 3,486 differentially expressed genes (DEGs) were identified based on transcriptome analysis of O. ocellatus. We identify metabolism-related DEGs using GO and KEGG enrichment analyses. Then, we construct protein–protein interaction networks to search the functional relationships between metabolism-related DEGs. Finally, we identified ten hub genes related to multiple gene functions or involved in multiple signal pathways, and verified them using quantitative RT-PCR. Protein–protein interaction networks were first used to study the effects of brood-care behavior on metabolism in the process of growing of O. ocellatus larvae, and the results provide us valuable genetic resources for understanding the metabolic processes of invertebrate larvae. The data lays a foundation for further study the brood-care behavior and metabolic mechanisms of invertebrates.